The Effectiveness of A Combination of Lemon (Citrus) Aromatherapy and Acupressure Massage in Reducing Emesis Gravidarum in Pregnant Women - Ifalahma, Darah; Yuliana, Ana; Rahayuningrum, Indriyati Oktaviano; Asri, Novia Kartika Hayu (GLOBAL HEALTH SCIENCE GROUP, 2024)
Nausea and vomiting in pregnant women (emesis gravidarum) occurs in 60-80% of primigravidas and 40-60% of multigravidas. Emesis gravidarum if not treated immediately will develop into hyperemesis and can result in impaired fetal growth, the fetus dies in the womb and the fetus may experience congenital abnormalities. One of the therapies that is safe and can be given to pregnant women who experience emesis gravidarum is by giving lemon aromatherapy and acupressure massage. Objective to determine the effectiveness of a combination of lemon (citrus) aromatherapy and acupressure massage in reducing emesis gravidarum in pregnant women. The research design used an experimental method with a one group pretest-posttest design. The independent variable is a combination of lemon aromatherapy and acupressure massage, the dependent variable is emesis gravidarum. The sampling technique used a purposive sampling technique, a sample of 10 first trimester pregnant women. The research instrument used lemon aromatherapy media, acupressure massage action schedule sheet, and Pregnancy Unique Quantification of Emesis (PUQE-24). The data analysis used is the t-test. The average incidence of emesis gravidarum before being given therapy was 9.3 (moderate degree category), the average incidence of emesis gravidarum after being given therapy was 5.5 (mild degree category). The results of the analysis using the t-test, the p-value < α, namely 0.000 < 0.05, which means that there is an effect of giving a combination of lemon (citrus) aromatherapy and acupressure massage to reducing emesis gravidarum. The combination of lemon (citrus) aromatherapy and acupressure massage is effective in reducing emesis gravidarum in first trimester pregnant women.